Efficacy of Short Novel Antimicrobial Peptides in a Mouse Model of Staphylococcus pseudintermedius Skin Infection - Mingyu Ouyang; Fangrong Wu; Changmin Hu (MDPI AG, 2024)
As the clinical application of antibiotics for bacterial skin infections in companion animals becomes increasingly prevalent, the issue of bacterial resistance has become more pronounced. Antimicrobial peptides, as a novel alternative to traditional antibiotics, have garnered widespread attention. In our study, synthetic peptides ADD-A and CBD3-ABU were tested against Staphylococcus pseudintermedius skin infections in KM mice. ADD-A was applied topically and through intraperitoneal injection, compared with control groups and treatments including CBD3-ABU, ampicillin sodium, and saline. Wound contraction, bacterial counts and histology were assessed on days 3 and 11 post-infection. ADD-A and ampicillin treatments significantly outperformed saline in wound healing (p < 0.0001 and p < 0.001, respectively). ADD-A also showed a markedly lower bacterial count than ampicillin (p < 0.0001). Histologically, ADD-A-applied wounds had better epidermal continuity and a thicker epidermis than normal, with restored follicles and sebaceous glands. ADD-A's effectiveness suggests it as a potential alternative to antibiotics for treating skin infections in animals.